Generation Z’s Understanding of Qur'anic Verses and Hadiths Regarding Zakat al-Mal: A Case Study in Banda Aceh - Insani, Muhammad Fitrah; Ilyas, Fithriady; Syahputra, Hendra (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This study examines the level of understanding among Generation Z in Banda Aceh regarding Qur’anic verses and hadiths related to zakat mal, utilizing a quantitative approach based on seven cognitive indicators: interpreting, explaining, exemplifying, classifying, summarizing, comparing, and inferring. Data were collected through an online questionnaire distributed via Google Forms to 105 respondents. The results indicate a moderate level of comprehension, with the following scores: explaining (69.20%), classifying (68.95%), inferring (68.69%), exemplifying (68.25%), comparing (68.06%), summarizing (67.04%), and interpreting (66.98%). Explaining emerged as the strongest indicator, while interpreting was the weakest. Although the respondents demonstrated a fair understanding of Zakat al-Mal, further educational efforts are needed to deepen both their conceptual and contextual understanding of this Islamic obligation. This study provides empirical insights for educational institutions and religious authorities to enhance Zakat al-Mal literacy among Generation Z and serves as a foundation for future research on the socio-economic application of Zakat.